ANALISIS PENGGUNAAN SARANA DAN PRASARANA DALAM MENUNJANG PELAYANAN ADMINISTRASI - Anisa Puspita Sari; Christian Wiradendi Wolor; Marsofiyati (Politeknik Negeri Madiun, 2023)
The purpose of this study was to determine the constraints in the use of office facilities and infrastructure in administrative service activities at the Operational Unit of the Bank Tabungan Negara, to determine the ability of employees to improve the quality of administrative services, and to choose the efforts made by companies in carrying out maintenance of facilities and infrastructure. The research method used is qualitative with a descriptive analysis approach. Data collection was obtained from various data such as literature studies and observations. The results of the study show that there are various obstacles faced by employees in using office facilities and infrastructure, multiple efforts made by employees affect the quality of administrative services, and the company's efforts to maintain office facilities and infrastructure affect administrative service activities.